jweiffenbach/PlioMIP2-SouthernOcean ... - Weiffenbach, J. E. (Zenodo, 2024)
Python code (Jupyter notebooks) and processed PlioMIP2 data used for analysis of the Southern Ocean of the PlioMIP2 ensemble in Weiffenbach et al. (2024). The code and data has been used for data analysis and creating the figures of the above manuscript, including the supplementary material. The filename of the Jupyter notebooks lists the figure(s) made with the notebook. The original PlioMIP2 data provided by individual PlioMIP2 modelling groups is available upon request from Alan M. Haywood (a.m.haywood@leeds.ac.uk), with the exception of IPSL-CM6A, EC-Earth3-LR and GISS2.1G. PlioMIP2 data from IPSL-CM6A, EC-Earth3-LR and GISS2.1G can be obtained from the Earth System Grid Federation (ESGF) (https://esgf-node.llnl.gov/search/cmip6/). The links to SST reconstruction data as well as observational sea-ice data are provided in the code and manuscript. ...